Diode behavior and nonreciprocal transmission in nonlinear elastic wave metamaterial. (June 2019) - Li, Zhen-Ni; Yuan, Bo; Wang, Yi-Ze; Shui, Guo-Shuang; Zhang, Chuanzeng; Wang, Yue-Sheng
Highlights: The band structures are obtained by the transfer matrix method and the transmission coefficients are achieved by the stiffness matrix method. Experiments are performed for comparison with the theoretical results. The nonreciprocal transmission of elastic waves is realized by enlightenment of an acoustic diode. Abstract: In this investigation, the nonreciprocal transmission of elastic waves is realized by enlightenment of an acoustic diode. The phenomenon can be found in a nonlinear elastic wave metamaterial which consists of a linear phononic crystal attached by a nonlinear elastic medium. The structural asymmetry and material nonlinearity break the inherent reciprocity. The multi-displacements coupling of elastic waves in solids makes the problem more complicated in mathematics, but with showing interesting physical phenomenon. The elastic waves with the fundamental and double frequencies can be generated by the interaction between an incident longitudinal wave and the material nonlinearity. Based on the Bloch's law and continuity conditions, the band structures are obtained by the transfer matrix method and the transmission coefficients are achieved by the stiffness matrix method. Especially, experiments are performed for comparison with the theoretical results. This research may be helpful to design practical devices with nonreciprocal transmission of the elastic wave metamaterial. Graphical abstract: The transmission coefficient for the incident longitudinal wave from the left boundary, which shows the fundamental and double frequency waves are zero in the frequency region with nonreciprocal transmission.Image, graphical abstract